KAJIAN SENI DAN BUDAYA PADA HINGGI DAN LAU DALAM UPACARA ADAT MASYARAKAT SUMBA TIMUR - Putu Diah Ari Kusumadewi; Sri Wening (Journal of Visual Art and Design, 2023)
Hinggi and lau, as East Sumba woven fabrics, are inseparable from the cultural identity contained in the motifs. In order to understand this culture, the symbolic meanings of the various motifs of hinggi and lau need to be understood. This study examined the hinggi and lau motifs in terms of visual analysis (contour), meaning (content), and background (context). The research method used was systematic literature review by analyzing selected articles using the PRISMA method and going through the identification, screening, eligibility, and inclusion stages with exclusion and inclusion criteria. The results showed that the physical form (contour) of hinggi and lau motifs varied, such as horse, chicken, human, and even skull motifs. These motifs represent meanings (content) related to life, death, and nature. All the meanings and motifs come from the Marapu belief system of East Sumba (context). Hinggi and lau, as cultural heritage, can adapt to change. Through this research, the authors recommend to relevant parties that the motives and functions of hinggi and lau themselves cannot be separated from the philosophical values contained therein, because they reflect the cultural identity of the people of East Sumba.